PRELIMINARY STUDY OF JURIDICAL ASPECTS OF RENEWABLE ENERGY DRAFT LAW IN INDONESIA : AN ACADEMIC PERSPECTIVES - Rosyid Ridlo, Al Hakim; Eko, Ariyanto; Yanuar Zulardiansyah, Arief; Aming, Sungkowo; Trikolas, Trikolas (Faculty of Sharia and Law UIN Sunan Gunung Djati Bandung, Indonesia, 2022)
Energy is an absolute necessity used in the survival of daily human life. The need for electrical energy in Indonesia continues to increase with economic growth and population increase. Indonesia's electricity demand is projected to increase more than seven times to 1,611 TWh in 2050. Through Commission VII of the House of Representatives of the Republic of Indonesia (DPR RI), the Indonesian government is drafting a Renewable Energy (RE) Bill. This rule provided a more detailed and in-depth explanation of the rules in terms of developing New and Renewable Energy (NRE) in Indonesia. This study critically reviews the formal juridical or regulatory aspects of Indonesia's Renewable Energy law (called RUU-EBT). This writing methodology is based on a literature review and data collected from relevant regulations and proposes the conclusion from relevant and expected regulations.